Relation of MDA as Oxidative Stress Marker with Lipid Profile in a Diabetic Patient - M. Azeez , Reem; K. Al-Hashemi , Wisam; F. R. Al-Auqbi , Tawfeeq; Jebali , Jamel (Al-Nahrain Journal of Science, 2023)
Type-2 diabetes mellitus (T2DM) is a disease accompanied by induced oxidative stress (OS) conditions. A reduction in antioxidant activity characterizes the OS conditions. Antioxidants protect cell components from the harmful effects of reactive oxygen species (ROS). The oxidation of the lipid components by ROS has the potential to generate malondialdehyde (MDA). The assessment of MDA (which is a byproduct of lipid peroxidation) may serve as a sign of oxidative damage. This can shed light on the impact of ROS on lipids. This study aims to elucidate the correlation between MDA oxidative stress biomarkers and lipids in individuals diagnosed with type-2 diabetes mellitus. The study comprises two case groups of 30 diabetic patients, 30 obese patients, and 30 healthy patients as the control group. The levels of MDA in the plasma specimens are measured. The serum glucose, serum lipid, and glycated haemoglobin (HbA1c) are evaluated for these groups. The results among patients with and without T2DM are analyzed with regard to age and BMI. The concentration of the MDA is [17.08 ± 1.989 (nmol/ml)] for diabetic patients, [16.08 ± 2.049 (nmol/ml)] for obese patients, and [12.12 ± 1.508 (nmol/ml)] for control patients. A statistically significant difference of p